8. REVIEW OF CLINICAL AND PARACLINICAL CHARACTERISTICS AND TREATMENT RESULTS OF STAPHYLOCCOCUS AUREUS INFECTIONS IN THE SURGICAL INTENSIVE CARE DEPARTMENT OF NGHE AN OBSTETRICS AND PEDIATRIC HOSPITAL FROM 1/2020 TO 8/2023 (Vietnam Journal of Community Medicine, 2024)
Objectives: (1) Describe the clinical and paraclinical characteristics of Staphylococcus aureus infection treated at the Department of Surgical Intensive Care; (2) Comment on the treatment results of Staphylococcus aureus infection at the Department of Surgical Intensive Care, Nghe An Obstetrics and Pediatrics Hospital.Subjects and methods: Retrospective and cross-sectional study. Convenient sampling of 46 patients from newborns to 15 years old diagnosed with S.aureus infection treated at the Department of Surgical Intensive Care, Nghe An Obstetrics and Pediatrics Hospital. Research period from 1/2020 to 8/2023.Results: S.aureus infection is diverse, the primary infection is mostly from the skin - soft tissue with 80.6%; respiratory 19.4%. Clinical presentation upon admission is fever 91.3%; 80.6% of isolated S.aureus strains are resistant to Methicillin. Completely sensitive antibiotics: Vancomycin, Levofloxacin and Linezolid; 100% of patients have Vancomycin MIC ≤ 1. Treatment results: 93.5% of patients have good treatment results; 6.5% of patients need to be transferred to the higher level; no patients died; 80.5% of patients had indications for surgical intervention; 63% of patients had no metastatic foci.Conclusion: S.aureus infection from skin - soft tissue with 80.6%; respiratory 19.4%; Completely sensitive antibiotics: Vancomycin, Levofloxacin and linezolid; 100% of patients had MIC Vancomycin ≤ 1. Treatment results were 93.5% of patients with good treatment results; 6.5% of patients needed to be transferred to the higher level.
Keywords: Staphylococcus aureus; Vancomycin MIC